2014
DOI: 10.1136/archdischild-2013-304878
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin in isoimmune haemolytic disease of newborn: an updated systematic review and meta-analysis

Abstract: Efficacy of IVIg is not conclusive in Rh haemolytic disease of newborn with studies with low risk of bias indicating no benefit and studies with high risk of bias suggesting benefit. Role of IVIg in ABO disease is not clear as studies that showed a benefit had high risk of bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 31 publications
0
40
0
1
Order By: Relevance
“…In a meta-analysis by Yang et al, immunoglobulins showed an increased risk for NEC (OR 4.53; 95% CI, 2.34-8.79; p < 0.001), but not for final mortality [39]. A recent systematic review advocates further well-designed studies before conclusive advice can be given about the treatment of HDFN with intravenous immunoglobulins [40].…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%
“…In a meta-analysis by Yang et al, immunoglobulins showed an increased risk for NEC (OR 4.53; 95% CI, 2.34-8.79; p < 0.001), but not for final mortality [39]. A recent systematic review advocates further well-designed studies before conclusive advice can be given about the treatment of HDFN with intravenous immunoglobulins [40].…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%
“…The importance of Rh disease varies widely with the prevalence of Rh-negative maternal status, but the issue of affordable prophylaxis is clearly a priority for many LMICs. The lack of routine maternal and neonatal blood testing in many LMICs is also a barrier, and also impacts the management of ABO incompatibility as a risk factor for serious NNJ [7,32,53,56,57,58,59]. …”
Section: The Present and The Future In Preventing Serious Nnjmentioning
confidence: 99%
“…To be effective, a phototherapy device should produce specific blue-light wavelengths (peak emission: 450 ± 20 nm), preferably in a narrow bandwidth to about 80% of an infant's body surface area, and have intensive irradiance of at least 30 μW/cm 2 /nm (from either a single or multiple phototherapy units) (32). Intravenous immunoglobulins have been proposed as a useful therapy in reducing the need for ET/RET, but existing evidence remains inconclusive (33).…”
Section: Discussionmentioning
confidence: 99%